The role of colonial state in the emergence of modern Minna town 1910-1960 / Salihu Ibrahim and Ahmad Zaharuddin Sani Ahmad Sabri - Ibrahim, Salihu; Ahmad Sabri, Ahmad Zaharuddin Sani (Universiti Teknologi MARA, Kedah, 2018)
Historically some towns owe their emergence to such developments like warfare, trade and commerce while others emerged because of geographical or military factors. Apologist of colonialism and bourgeoisie scholars’ emphasized the role of colonial state in the establishment and emergence of town/cities in Africa. This paper adds voice to the existing literature and further argued that it did not just found such settlements but improved on the agglomeration process following its various policies. To successfully conduct this study critical analysis of secondary sources is employed. The research aim at an examination of the growth and development of Minna town in the face of modernization, urbanization and changing socio-economic and political environment, it traced the emergence of the town to colonial era in 1910 following the British conquest of the area and consequent establishment of colonial administrative structures. The significance of the paper lies in its ability to unravel the historicity of the origin of Minna and to point out the